MicroRNAs as cancer therapeutics: A step closer to clinical application. (28th October 2017) - Catela Ivkovic, Tina; Voss, Gjendine; Cornella, Helena; Ceder, Yvonne
Abstract: During the last decades, basic and translational research has enabled great improvements in the clinical management of cancer. However, scarcity of complete remission and many drug-induced toxicities are still a major problem in the clinics. Recently, microRNAs (miRNAs) have emerged as promising therapeutic targets due to their involvement in cancer development and progression. Their extraordinary regulatory potential, which enables regulation of entire signalling networks within the cells, makes them an interesting tool for the development of cancer therapeutics. In this review we will focus on miRNAs with experimentally proven therapeutic potential, and discuss recent advances in the technical development and clinical evaluation of miRNA-based therapeutic agents. Highlights: Different genes can be simultaneously regulated by a single miRNA. Regulatory non-coding RNAs, particularly miRNAs, are implicated in cancer progression. Numerous preclinical trials highlight miRNAs as potentially useful clinical tools. Three miRNA-based cancer therapeutics are under evaluation in phase I clinical trials.